UNDERSTANDING OF ONLINE MEDIA JOURNALIST IN MANGGARAI REGENCY ABOUT THE JOURNALISTIC CODE OF ETHICS - Jahang, Melania Maria Dolorosa; Sayuti, Syaifuddin (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Ethics is a system of moral principles. They affect how people make decisions and lead their lives.Ethics can be interpreted as a value or norm that must be possessed by every human being, includingjournalists. In carrying out their duties, journalists must still refer to the rules that have been made. Theserules are written in the journalistic code of ethics established by the Indonesian Press Council, which appliesto all journalists in Indonesia, including those in Manggarai, Flores, NTT. The journalistic code of ethicsplays a very important role in the world of the press where it serves as an operational guideline in thepreservation of the integrity and professionalism of the journalist, so that it must be understood andimplemented by journalists. This study aims to identify and analyze the application of journalistic code ofethics, to identify and analyze violations in its application, and to identify and analyze solutions taken inpreventing and dealing with violations of journalistic code of ethics by Manggaraian's local mediajournalists. The research method used in this research is descriptive qualitative. The results showed that theimplementation of the journalistic code of ethics in the local media of Manggarai, Flores, NTT was quitegood, although there were still several violations of the journalistic code of ethics that occurred. So far, thehandling of each violation has only been in the form of a warning, while prevention so that there is noviolation of the journalistic code of ethics is in the form of socialization of the code of ethics to journalists.Suggestions are given that in the recruitment of journalists, strict selection must be carried out in accordancewith the national journalist competency test standards so that the working journalists are truly competentand qualified journalists, also aimed at the Manggarai government to facilitate any activities related tosocialization and education. journalistic code of ethics.